2024
DOI: 10.1101/2024.02.07.579323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large- and Small-Animal Studies of Safety, Pharmacokinetics (PK), and Biodistribution of Inflammasome-Targeting Nanoligomer in the Brain and Other Target Organs

Sydney Risen,
Breonna Kusick,
Sadhana Sharma
et al.

Abstract: The human immune system is the key line of defense in the body against infections and disease and is critical for our survival. However, immune malfunction or misrecognition of healthy cells and tissue, termed autoimmune disease, is implicated in more than 80 disease conditions and multiple other secondary pathologies. While pan-immunosuppressive therapies like steroids offer some relief for systemic inflammation for some organs, many patients never achieve remission and such drugs do not cross the blood-brain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We have shown that NI112 reduces pro-inflammatory astrocytes/microglia even in prion-treated mice, 61 agingassociated neuropathology and AD, 64 and EAE mice 63 (models of severe neurodegeneration), and that this is associated with cognitive improvements. Moreover, the high binding specificity (K D ~5 nM 60,62,72 ), minimal off-targeting, 60,62,65 high safety profile, 65 lack of any immunogenic response or accumulation in first pass organs, 65 absence of any observable histological damage to organs even for long (>15-20 weeks) treatments, [60][61][62]65 and facile delivery to the brain to counter neuroinflammation, 58,61,63,65 make Nanoligomers and specifically the NI112 cocktail a promising, safe and targeted approach to mitigate neuropathological inflammation, as well as microglial and astrocytic activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that NI112 reduces pro-inflammatory astrocytes/microglia even in prion-treated mice, 61 agingassociated neuropathology and AD, 64 and EAE mice 63 (models of severe neurodegeneration), and that this is associated with cognitive improvements. Moreover, the high binding specificity (K D ~5 nM 60,62,72 ), minimal off-targeting, 60,62,65 high safety profile, 65 lack of any immunogenic response or accumulation in first pass organs, 65 absence of any observable histological damage to organs even for long (>15-20 weeks) treatments, [60][61][62]65 and facile delivery to the brain to counter neuroinflammation, 58,61,63,65 make Nanoligomers and specifically the NI112 cocktail a promising, safe and targeted approach to mitigate neuropathological inflammation, as well as microglial and astrocytic activation.…”
Section: Introductionmentioning
confidence: 99%
“…40,[53][54][55] Inflammasome inhibition has been intensely investigated as a novel target, as well as a common cure for a range of neurodegenerative and autoimmune diseases, 56,57 and using NF-κB and NLRP3 mRNA targeting and translation-inhibiting Nanoligomer combination (NI112) is a safe, effective, and targeted approach. [58][59][60][61][62][63][64][65] However, even other inflammasome-targeting smallmolecule therapeutics (e.g., MCC950) are limited by: 1) potential off-target effects; [66][67][68] and 2) the fact that they target only NF-κB or NLRP3 alone. NI112, an RNA therapeutic that crosses the blood-brain barrier, addresses problems with pan immunosuppressive therapies (such as steroids), and the cocktail potently inhibits neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42] Nanoligomers utilize peptide nucleic acids (PNAs) as the sequence-specific binding component that demonstrate strong hybridization and specificity to their RNA (or DNA) sequence targets, 43 and exhibit no known enzymatic cleavage, leading to increased stability in human blood serum and mammalian cellular extracts. 44 Given the low K D , 35,36,43 high binding specificity, minimal off-targeting, 35,36 lack of any immunogenic response or accumulation in first pass organs, 34 absence of any observable histological damage to organs even for long (>15-20 weeks) treatments, [34][35][36]40 and facile delivery to the brain to counter neuroinflammation, 34,[37][38][39][40][41][42] we have demonstrated that Nanoligomers are a safe and targeted approach to screen for therapeutic targets in organoids and rodents for multiple neurodegenerative diseases aboard the International Space Station (ISS).…”
mentioning
confidence: 99%
“…Nanoligomer-based High-Throughput Screening is a Safe and Targeted Approach. Nanoligomer™ therapeutic platform generates safe, targeted, 34 and highly-specific (K D 3.37 nM 35,36 ) RNA-targeting molecules for facile delivery to targeted organs and both up-and downregulation of desired protein through translational and transcriptional regulation. [37][38][39][40][41][42] Nanoligomers utilize peptide nucleic acids (PNAs) as the sequence-specific binding component that demonstrate strong hybridization and specificity to their RNA (or DNA) sequence targets, 43 and exhibit no known enzymatic cleavage, leading to increased stability in human blood serum and mammalian cellular extracts.…”
mentioning
confidence: 99%